The impact of physician preferences and patient habits on the diffusion of new drugs - Magnus Johannesson; Douglas Lundin (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
We study the choice of drug for the treatment of high blood pressure (hypertension) in Sweden between 1988-1994. During this time period calcium antagonists and ACE-inhibitors increased their market shares at the expense of the older drugs diuretics and beta-blockers. We use a prescription micro dataset where both patients and physicians can be followed over time - an important feature since it allows us to study the impact of physician preferences and patient habits on the choice of drug. The choice of drug is unaffected by relative prices, indicating a moral hazard problem on the Swedish drug market characterized by a high degree of third-party financing. Physician preferences, measured as physician prescription history, are important for the choice of drug among new patients. Among existing patients the effect of physician preferences is mitigated by patient habit formation which slows down the diffusion of new drugs. Without habit effects the market share of calcium antagonists and ACE-inhibitors would have been more than 50% higher during our observation period (30% instead of the observed 19%).
Keywords: C25; I11; L10; O33; 330; pharmaceuticals; physician behavior; habit formation; mixed logit estimator; Pharmazeutisches Produkt; Innovationsdiffusion; Präferenztheorie; Ärzte; Preis; Schweden